2010
DOI: 10.1209/0295-5075/90/66001
|View full text |Cite
|
Sign up to set email alerts
|

Tunable dynamic fragility and elasticity in dense suspensions of many-arm-star polymer colloids

Abstract: A microscopic theoretical study of glassy dynamics in dense fluids of soft manyarm-star polymers is performed which elucidates the connection between local packing, shear elasticity and activated relaxation. A soft-jamming crossover is identified, below which particlesoftness-dependent apparent power law concentration scaling of the shear modulus and supraexponential relaxation occur. Dynamic fragility varies over a remarkably wide range, increasing logarithmically with star functionality. Beyond the soft-jamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Note that jamming in soft hairy materials has been also discussed in the context of activated hoping with theoretical ideas based on mode coupling, and a linear dependence of storage modulus on volume fraction was reported. 89 More generally, it seems that the linear dependence of G p on concentration is typical of jammed states 87,88,90,91 and the present soft and short cylinders conform to the emerging picture. Such a finding certainly opens a new scenario of jamming in anisotropic colloids at rest, in addition to previous experimental works addressing the jammed state induced by shear flow.…”
Section: Linear Viscoelastic Responsementioning
confidence: 62%
“…Note that jamming in soft hairy materials has been also discussed in the context of activated hoping with theoretical ideas based on mode coupling, and a linear dependence of storage modulus on volume fraction was reported. 89 More generally, it seems that the linear dependence of G p on concentration is typical of jammed states 87,88,90,91 and the present soft and short cylinders conform to the emerging picture. Such a finding certainly opens a new scenario of jamming in anisotropic colloids at rest, in addition to previous experimental works addressing the jammed state induced by shear flow.…”
Section: Linear Viscoelastic Responsementioning
confidence: 62%
“…Limiting analytic analysis of the single-particle theory has shown that the barrier height for hard spheres (but not soft spheres 30 ) scales with the inverse of the localization length: F B ∼ σ/r loc . 22,58 We find that this scaling works very well for the r-directional barrier when r 0 = σ, but fails for the R-direction barrier at that initial separation, and for both barriers at all other initial separations.…”
Section: Model Calculationsmentioning
confidence: 99%
“…7 replots the Kramers times in a normalized format to expose the relative rate of increase with volume fraction and r 0 , a representation relevant to the question of "dynamic fragility." 1,28,30,61 The fragility is weakest for an initial interstitial configuration, and strongest when the two particles are initially in contact.…”
Section: B Mean Barrier Hopping Timementioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Softness was also shown to have a prominent influence on effective interactions, both in microgels [4][5][6][7] and star polymers. 8,9 From a dynamical perspective, the presence of an inverse correlation between softness and dynamical fragility in the supercooled regime was put forward some years ago, 10,11 and it is still a very debated issue both in experiments 12,13 and in simulations 14,15 . In addition, soft colloids can explore a variety of high density states, a) Electronic mail: nicoletta.gnan@cnr.it above the so-called jamming point [16][17][18] , here loosely defined as the limit condition in which particles can fill the available space without deforming.…”
Section: Introductionmentioning
confidence: 99%